CD14 and toll-like receptor 4: a link between infection and acute coronary events?. Issue 9 (13th August 2004) - Arroyo-Espliguero, R; Avanzas, P; Jeffery, S; Kaski, J C
Abstract : The CD14 receptor is a pattern recognition molecule in the innate immune response against microorganisms and other exogenous and endogenous stress factors. The most important CD14 signalling co-receptor is toll-like receptor 4 (TLR4), which activates, among others, the nuclear factor κB (NF-κB) inflammatory pathway. Besides its role in innate immunity and host defence, the proinflammatory cytokines expressed upon TLR4/NF-κB pathway activation exert proatherogenic effects. The CD14 C(–260)T promoter and TLR4 Asp299Gly functional polymorphisms have been recently implicated in the development of cardiovascular events, suggesting that the genetically determined inflammatory response against pathogens or their antigens may have a major role in atherogenesis and subsequent acute events. Is the association of these polymorphisms with cardiovascular disease more evidence for the implication of infection, especially by Gram negative bacteria, in the development of acute coronary events? This article reviews the molecular basis, biological functions, and clinical implications of the CD14/TLR4 polymorphisms in the development of cardiovascular events.